ADDRESSING GENDER BIAS ISSUES IN ELEMENTARY SCHOOL EFL TEXTBOOKS: AN ANALYSIS OF GROW WITH ENGLISH - Nashriyah; Maulida, Rizka; Setia Ningsih, Yuni; Qismullah Yusuf, Yunisrina (Humanities & Social Sciences Reviews, 2020)
Purpose of the study: A textbook is a book containing comprehensive teaching-learning materials for a certain subject which is regularly used by both teachers and students at school. Textbooks should not contain unfair content or matters, such as gender bias. This study was conducted to examine the extent to which gender bias appears in the EFL textbook mostly employed in Aceh, Indonesia. Methodology: This research was aimed at investigating the representation levels of gender in English elementary textbooks of Grow with English book 4, book 5, and book 6. A content analysis method was used, for which every page of the textbooks was investigated to explore the five aspects of visibility, priority, feminine/masculine generic construction, activity, and occupation. Main Findings: The result of the investigation shows that every textbook contains gender bias of various representation levels. Males dominated three categories, namely priority, activity, and occupation. Meanwhile, females are only dominant in the visibility category. The results suggest that the EFL textbooks mostly used in Aceh are still not free from gender bias issues. Applications of this study: Indonesia is a country where English is used as a Foreign Language (EFL). Indonesian schools are apt to use textbooks written by Indonesian authors as the major source for English instruction in schools. Therefore, researchers should focus their attention on the content of English textbooks used in schools because they become the guidance for these students in learning. Novelty/Originality of this study: The results of the study suggest that the EFL textbook should be considered for revision to ensure that it is free from unfair content. This is aimed at national textbook designers when they have to produce a textbook for Indonesian learners so that the books they make available to schools are free from gender bias issues in the textbooks.